100 TOTAL LYMPHOCYTES COUNT (TLC) PREDICTS THE OVERALL SURVIVAL AFTER CHEMORADIOTHERAPY IN ESOPHAGEAL CARCINOMA PATIENTS. (17th September 2021) - Nishida, Masato; Sato, Shinsuke; Higashizono, Kazuya; Taki, Yusuke; Nagai, Erina; Wataanbe, Masaya; Ohata, Ko; Kanemoto, Hideyuki; Oba, Noriyuki
Abstract:  : Lymphocytes play a critical role in the host immune system, and a decrease in number of lymphocytes, caused by malnutritional status and chemoradiotherapy (CRT) leads to immunosuppression. Immunosuppression could enhance the cancer development and progression. Previous studies demonstrated that lymphopenia was associated with worse prognosis in the pancreatic, lung, head and neck, and rectal cancer, but little is known about esophageal cancer. Methods: There were 298 patients of esophageal malignant tumors, who had been initially treated with chemoradiotherapy (CRT) between January, 2007 and December, 2018. The total lymphocyte counts (TLC) before CRT and the nadir value during 6 weeks after CRT along with other clinical and treatment characteristics of these 298 patients, were retrospectively evaluated in relevance with the overall survival (OS) after CRT. Results: The median TLC before and after CRT were 1469 (range 456–4710)/mm 3 and 354 (range 21–1500)/mm3, respectively. When the patients were stratified with the threshold value of 1500/mm3 of pretreatment TLC, the Log-Rank test showed significant difference in OS between these 2 groups (OS 48.7% vs 36.6%, p = 0.011). In addition, the CTCAE grade of lymphopenia exceeding 3 after CRT was associated with worse OS even in the group with pretreatment TLC level more than 1500/mm 3 . The multivariate analysis showed that the significant prognostic factors of OS were cN, cM, additional esophagectomy and pretreatment TLC. Conclusion: The decease of pretreatment TLC was significantly associated with worse OS when the patients of esophageal cancer were initially treated with CRT.